Democratic Deliberation in Deeply Divided Societies From Conflict to Common Ground - Ugarriza, Juan E.; Caluwaerts, Didier; SpringerLink (Online service) (London : Palgrave Macmillan UK : Imprint: Palgrave Macmillan, 2014)
Through case-analysis and cross-sectional assessment of eleven countries this collection explores the most deeply divided societies in the world in order to highlight what deliberative democracy looks like in a deeply divided society and to understand the conditions that deliberative democracies could realistically emerge in difficult circumstances.
Keywords: Political science; Political theory; Political communication; Comparative politics; Democracy; Peace; Political Science and International Relations; Democracy; Political Theory; Political Science; Conflict Studies; Comparative Politics; Political Communication